An Overview of Mental Calculation Strategies and the Frequency of Their Application - Jurić, Josipa; Pjanić, Karmelita (Revija za elementarno izobraževanje, 2023)
The paper aims to explore mental calculation strategies and the frequency of their application in tasks. In the paper, we categorized mental calculation strategies related to four basic mathematical operations, looked at several different strategies used by students in a test containing mental calculation tasks, and presented an overview of the interview results. We also analyzed age-related differences in the number of strategies applied by participants. It was found that Mathematics in school does not always contribute to the development of and flexibility in the use of mental calculation strategies. One apparent reason is student preference for previously acquired written algorithms.
Keywords: mental calculation, categorization of mental calculation strategies, school Mathematics, teaching mental calculation, frequency of application of mental calculation strategies